Community Empowerment Through Super Ganepo Umkm in Jorong Padang Kandi, Nagari VII Koto Talago, Guguak District, Lima Puluh District - Andini, Puti; Gani, Maulid Hariri; Oktayanty, Yetty (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research discusses "Community Empowerment through Super Ganepo UMKM in Jorong Padang Kandi, Nagari VII Koto Talago, Guguak District, Limapuluh Kota Regency". The aim of this research is to describe the role of Super Ganepo UMKM in the community economy and the forms of community empowerment that occur in Jorong Padang Kandi, Nagari VII Koto Talago, Guguak District, Limapuluh Kota Regency. The theory used in this research is Chambers' empowerment theory. The method used is a qualitative method, with data collection techniques of observation, interviews, literature study and documentation. The results of this research show that it started with the success of one of the people who tried to create a food called Ganepo. This success was well received by the community, whose presence is currently increasing through empowerment. Empowerment occurs not only from community to community but there is a role for the government in it, such as facilitating the business to become a Super Ganepo UMKM as well as providing training and providing tools to improve Super Ganepo UMKM. Currently, the existence of Super Ganepo UMKM has a very important role in the social and economic aspects of the community in Jorong Padang Kandi in facilitating interaction in the empowerment process, equality for each member of the group, reducing unemployment rates, providing employment opportunities and jobs in increasing community welfare and improving quality. society's life in a better direction.